Developmental dynamic transcriptome and systematic analysis reveal the major genes underlying isoflavone accumulation in soybean - Chen, Heng; Liu, Changkai; Li, Yansheng; Wang, Xue; Pan, Xiangwen; Wang, Feifei; Zhang, Qiuying (Frontiers in Plant Science, 2023)
Soy isoflavone, a class of polyphenolic compounds exclusively occurred in legumes, is an important bioactive compound for both plants and human beings. The outline of isoflavones biosynthesis pathway has been drawn up basically in the previous researches. However, research on the subject has been mostly restricted to investigate the static regulation of isoflavone content in soybean, rather than characterize its dynamic variation and modulation network in developing seeds. In this study, by using eight recombinant inbred lines (RIL), the contents of six isoflavone components in the different stages of developing soybean seeds were determined to characterize the dynamic variation of isoflavones, and investigate the isoflavones accumulation pattern at physiological level. Meanwhile, via integrating and analyzing the whole genome expression profile of four lines and 42 meta-transcriptome data, we: 1) obtained 4 molecular modules strongly correlated with isoflavone accumulation; 2) identified 28 novel major genes that could affect the accumulation of isoflavones in developing seeds free from the limitation of environments; 3) discussed the dynamic molecular patterns regulating isoflavones accumulation in developing soybean; 4) expanded the isoflavone biosynthesis pathway. The results not only promote the understandings on the biosynthesis and regulation of isoflavones at physiological and molecular level, but also facilitate to breed elite soybean cultivars with high isoflavone contents.